Psychosocial risk factors in workers of footwear trading companies in Tungurahua-Ecuador (UTC Prospectivas: Journal of Administrative and Economic Sciences, 2025)
The study of psychosocial risk factors emerges as a crucial topic for academic research, organizational practice, and employee well-being; hence, the main objective of this study is to establish the factors that influence the current level of psychosocial risk experienced by workers in trading companies in the footwear sector in the province of Tungurahua. From January to July 2024, the official instrument of the Ministry of Labor of Ecuador for psychosocial evaluation was applied to 237 workers in the nine cantons of the Province of Tungurahua in the central zone of Ecuador. This semi-structured questionnaire allowed us to collect crucial information on sociodemographic variables, variables associated with the company, and psychosocial work factors. The collected data were quantitatively analyzed using the analysis of variance and the multiple regression model. The results show three significantly different levels of psychosocial risk, with workers mostly experiencing medium and high-risk levels, which reflect a negative relationship with the job and emotional stability, as well as work organization. The quantification of psychosocial risk and the main factors inducing these levels could become the starting point for designing and implementing specific intervention programs for this critical economic sector, preventing future physical and mental health effects that will significantly impact performance and work commitment.
Keywords: Psychosocial risk factors; trading; well-being; occupational psychology